Implementasi Program Padat Karya Bagi Masyarakat Berpenghasilan Rendah (MBR) Dalam Perspektif Collaborative Governance di Kelurahan Manyar Sabrangan Kota Surabaya - Lafina, Alfonsus Rahanratu; Sholichah, Nihayatus; Wardhono, Hendro; Widyawati (Jurnal ilmiah Manajemen Publik dan Kebijakan Sosial, 2023)
The "Padat Karya" program is a labor-intensive development activity that relies more on human resources compared to machinery. The main goal of the program is to create employment opportunities for the community, especially those who have lost their income or regular jobs. This research employs a qualitative approach with a descriptive research type. It describes the Implementation of the "Padat Karya" Program for Low-Income Communities from the perspective of Collaborative Governance, referring to the theory of Van Metter & Van Horn. The results of this study indicate that the implementation of the "Padat Karya" Program has not been fully optimized. Factors such as supervision patterns, strengthening of resources, especially for low-income communities, and legal framework related to the technical guidelines of the "Padat Karya" Program within Collaborative Governance are criteria for success and failure. With the "Padat Karya" Program, the community, especially in Manyar Sabrangan Village, has increased their participation and are not solely reliant on government assistance. They can independently utilize the program that has been established to manage their own affairs in the long run, reducing their dependency on the government